Optimization of Non-Tax State Revenue in the Water Lease Section in the Marine Sector of Institution X Office - Jaya Frediyanto; Hero Priono; Gideon Setyo Budiwitjaksono (Universitas KH. Abdul Chalim Mojokerto, 2025)
Indonesia, as an archipelagic country, relies heavily on maritime transportation and shipping services. One crucial element in supporting the efficiency of the shipping sector is the optimization of non-tax state revenue (PNBP), particularly from water leases. This study aims to analyze water lease agreements and PNBP optimization strategies at Institution X Office. The study employed a qualitative approach, conducting in-depth interviews with five informants representing both regulators and service users. The results indicate that a significant decline in PNBP in 2025 will occur due to instability in rental rates and reduced interest in leasing from large business actors such as PT A and PT B. Additionally, several internal constraints were identified, including limited human resources, outdated information systems, and inflexible tariff policies. This study adopted Pricing and Revenue Optimization Theory to formulate ten optimization strategies, including strengthening price evaluation mechanisms, utilizing lost quote data, and the need for a zoning-based and market-sensitive tariff approach. It was concluded that the success of PNBP optimization depends not only on tariff policies but also on regulatory consistency, fiscal transparency, and sustainable use of marine space. This research provides a practical contribution to Institution X and the Ministry of Transportation in designing a PNBP management system that is efficient, fair, and adaptive to market dynamics.